2013
DOI: 10.1074/jbc.m112.405159
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein Convertases Process and Thereby Inactivate Formylglycine-generating Enzyme*

Abstract: Background:The ER-resident formylglycine-generating enzyme (FGE), essential for post-translational activation of all eukaryotic sulfatase enzymes, is N-terminally processed during secretion. Results: Processing is mediated by furin at a conserved R/K-YS-R/K2 cleavage site and leads to FGE inactivation. Conclusion: Processing serves to regulate the amount of FGE activity following ER exit. Significance: Processing is never complete, thus suggesting an extra-ER function of FGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Previous reports provide evidence that the NTE is required for ER retention through disulfide bond formation between Cys 50 and/or Cys 52 with ERp44 ( 32 ). The border between the NTE and the core is a proteolytic cleavage site for proprotein convertases such as furin and PACE ( 33 ). When FGE encounters these enzymes in the secretory pathway, the NTE is removed and the truncated core can be secreted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports provide evidence that the NTE is required for ER retention through disulfide bond formation between Cys 50 and/or Cys 52 with ERp44 ( 32 ). The border between the NTE and the core is a proteolytic cleavage site for proprotein convertases such as furin and PACE ( 33 ). When FGE encounters these enzymes in the secretory pathway, the NTE is removed and the truncated core can be secreted.…”
Section: Resultsmentioning
confidence: 99%
“…We discovered that in vitro , the full-length FGE had a propensity to aggregate at high concentrations, which led us to prepare the truncated core (cFGE). We were unsure whether this approach would be successful because previous results showed that the NTE is required for FGE activity in vitro ( 33 ). In our hands, the specific activity of Hs -cFGE (1,143 pkatal mg −1 , 33.3 kDa) was similar to Hs -FGE that contained the NTE (850 pkatal mg −1 , 36.9 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 20–30% of secreted FGE avoids proteolytic cleavage and remains active. 56 Secreted FGE can traffic back to the ER from the cell surface. Indeed, tissue-specific expression of FGE in FGE-null mice has been shown to activate sulfatases in nontransduced tissues, in this way acting as a paracrine agent.…”
Section: Mammalian Fge Activity Is Regulated By Protein Partnersmentioning
confidence: 99%
“…As a first step to address the variability of fGly conversion levels, we considered that differences in intracellular FGE levels might affect conversion yields. Wild-type human FGE is partially retained in the ER through interactions of its N -terminal region (called the N -terminal extension, NTE) with endoplasmic reticulum resident protein 44 (ERp44) [ 12 ]. This interaction can be abrogated by furin-mediated proteolytic cleavage at an internal site, allowing the remaining catalytically-active core enzyme to be secreted [ 11 ].…”
Section: Resultsmentioning
confidence: 99%